PEMODELAN PROSES SISTEM KEPAKARAN DOKTER - Julia Kurniasih; Yuni Ambar S; Wahit Desta; Yulius Nahak T; Faizul Ikhsan (PROSIDING SNAST, 2018)
Indonesian Doctors Association (IDI) as a professional organization requires an information system is used to store, process and display data of doctor's expertise. The patient’s needs in searching information about doctors, specialization and the schedule of practice; and the stake holder’s needs about information related to the doctor’s expertise must be fulfilled by the information system, in the form of website development. For the purpose of website development need to be modeled system processes that describe the structure and flow of data, rules, and procedures. Process modeling of expertise using flowchart. The modelling elements include actors (admin, doctors, patients and other users), roles (defining capacity of actors), activity (defining business process) and product (information provided by expertise system). The simulation of process modelling of expertise system illustrates the process searching information on the name of the practice institution, the license and schedule of practice. The practice permit can be checked through the local district health website. Other information displayed includes doctor's profile, devotion activity, research and publication; and that statistics.